English Calques in Bangla - Sarwar Morshed (Journal of Language Learning and Research (JOLLAR), 2019)
Two hundred years of colonial rule brought the Anglophones in close proximity to the Banglophones. This long time interaction resulted in bilingualism which ultimately paved the way for lexical penetration from English into Bangla. This influx is manifest in the corpus of the Bangla language. Viddyasagar in his Shobdosongroho (1823, Quoted in Musa and Ilyas, 2002:11) compiled a list of 40 English loanwords in Bangla. Within the timespan of nearly two centuries, according to Musa and Ilyas (2002), the lexical loan got multiplied by almost 88 times. Side by side borrowing direct anglicisms, Bangla has also borrowed hosts of indirect loans in the form of ‘calques’ or ‘translation loans’ from English. The prime focus of this paper is to trace the mechanisms by which Bangla produces calques from English sources. The results of this study reveal that Bangla has four types of calques – single-word, multi-word, phrasal, and acronymic. While our data mostly conform to the global typology of calques, interestingly enough, Bangla has constructed a special class of calques which we have dubbed as ‘Acronymic calques’. Translation acronyms are yet to be registered in the typology of calques. This curious calque type attested by our data can be added to the global typology of loan translations.